Climate sensitive growth and yield models in Canadian forestry: Challenges and opportunities - J.M. Metsaranta; M. Fortin; J.C. White; D. Sattler; W.A. Kurz; M. Penner; J. Edwards; W. Hays-Byl; R. Comeau; V. Roy (The Forestry Chronicle)
Growth and yield models in forest management planning are used to project future forest conditions and estimate quantities such as wood volume and biomass. These models are crucial for assessing forest sustainability, however, some models currently used in Canada do not adequately account for climate and other environmental variables, which limits their effectiveness under a changing climate. Climate-sensitive growth and yield models (CSGYMs) are therefore urgently needed to support forest management decisions. The Canadian Forest Service (CFS) has developed a strategic plan to advance climate-sensitive growth and yield modeling in Canada through collaboration with provincial and territorial agencies, as well as other partners. The primary objective of this plan is to provide a national-level modelling approach to predicting and managing forest growth, mortality, and other ecosystem services. The climate sensitive growth and yield modelling initiative emphasizes collaboration, open data, and open-source code principles to ensure widespread accessibility and uptake of models, thus contributing to the sustainable management of forest resources. This technical review reports on the status of growth and yield models currently applied in each province and territory, assesses the level of climate sensitivity associated with each of these models, synthesizes the relevant modeling approaches and input data required to implement climate sensitivity into these models, and suggests possible pathways for achieving CSGYM at a national scale. Widespread collaboration will be the key to advancing the development of CSGYMs.